2021
DOI: 10.1186/s12931-021-01640-z
|View full text |Cite
|
Sign up to set email alerts
|

Hermansky-Pudlak syndrome-2 alters mitochondrial homeostasis in the alveolar epithelium of the lung

Abstract: Background Mitochondrial dysfunction has emerged as an important player in the pathogenesis of idiopathic pulmonary fibrosis (IPF), a common cause of idiopathic interstitial lung disease in adults. Hermansky-Pudlak syndrome (HPS) is a rare autosomal recessive disorder that causes a similar type of pulmonary fibrosis in younger adults, although the role of mitochondrial dysfunction in this condition is not understood. Methods We performed a detailed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…5 D, E). Intracellular reactive oxygen species (ROS) are mainly generated in the mitochondria, and mitochondrial ROS levels were reported to be increased in the lung tissue of IPF and alveolar epithelial cells of HPS2 model mice [ 41 , 42 ]. Consistent with these reports, the accumulation of intracellular ROS was observed in HPS1 KO A549 cells (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 D, E). Intracellular reactive oxygen species (ROS) are mainly generated in the mitochondria, and mitochondrial ROS levels were reported to be increased in the lung tissue of IPF and alveolar epithelial cells of HPS2 model mice [ 41 , 42 ]. Consistent with these reports, the accumulation of intracellular ROS was observed in HPS1 KO A549 cells (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Proteomic analysis revealed that HPS1 patient-specific AOs could show impaired membrane trafficking and mitochondrial dysfunction. Abnormalities in membrane trafficking were observed in several hereditary interstitial lung diseases, such as SFTPC with I73T mutation and HPS, and mitochondrial dysfunction in AT2 cells was reported as a common phenotype [ 42 , 50 52 ]. Our results could reinforce the possibility of a relationship between abnormal membrane trafficking and mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Whether these changes are functionally important has been a subject of some debate, as maximal mitochondrial capacity typically far exceeds metabolic tissue demands even under stress conditions, and modest reductions in mitochondrial function induced by haploinsufficiency in mitochondrial genes do not accelerate aging phenotypes in unstressed animals ( 124 ). Interestingly, Liu and colleagues identified rare genetic variants in families with pulmonary fibrosis involved in the formation of mitochondrial ETC complex I ( 125 ), and Cuevas-Mora et al identified alterations in mitochondrial function in alveolar epithelial cells with mutations in adaptor protein complex 3 β1 (Ap3b1), a cause of Hermansky-Pudlak syndrome ( 126 ). Several groups have shown that the ISR is activated in response to mitochondrial ETC dysfunction in vitro and in vivo ( 127 138 ).…”
Section: Age-related Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Moreover, although hemophagocytic lymphohistiocytosis (HLH) patients, which show excessive immune activation, are reported to have mutations in AP3B1 [ 184 , 185 ], HPS patients or pearl mouse models rarely display HLH symptoms [ 186 , 187 ], indicating that AP3B1 variation might have different effects depending on the mutation and/or species affected. Recently, bioinformatic analysis revealed the putative role of AP3B1 in amyotrophic lateral sclerosis pathogenesis, a neurodegenerative disease that affects muscle movement [ 188 ] Alveolar epithelial cells with defective AP3B1 were found to display abnormal mitochondrial formation [ 189 ], while lung tissues showed increased matrix metalloproteinase activity [ 190 ], suggesting a potential role of AP3B1 in lung tissue. AP3B1 mutation was found to affect natural killer (NK) and NKT cell granule-associated protein release, which presumably explains the susceptibility to infection and lymphoma among HPS2 patients [ 191 ].…”
Section: Ap3 Complexmentioning
confidence: 99%